Marine bacteria from the French Atlantic coast displaying high forming-biofilm abilities and different biofilm 3D architectures. Issue 1 (December 2015) - Doghri, Ibtissem; Rodrigues, Sophie; Bazire, Alexis; Dufour, Alain; Akbar, David; Sopena, Valérie; Sablé, Sophie; Lanneluc, Isabelle
Abstract Background Few studies have reported the species composition of bacterial communities in marine biofilms formed on natural or on man-made existing structures. In particular, the roles and surface specificities of primary colonizers are largely unknown for most surface types. The aim of this study was to obtain potentially pioneering bacterial strains with high forming-biofilm abilities from two kinds of marine biofilms, collected from two different surfaces of the French Atlantic coast: an intertidal mudflat which plays a central role in aquaculture and a carbon steel structure of a harbour, where biofilms may cause important damages. Results A collection of 156 marine heterotrophic aerobic bacteria isolated from both biofilms was screened for their ability to form biofilms on polystyrene 96-well microtiter plates. Out of 25 strains able to build a biofilm in these conditions, only four bacteria also formed a thick and stable biofilm on glass surfaces under dynamic conditions. These strains developed biofilms with four different three - dimensional architectures when observed by confocal laser scanning microscopy:Flavobacterium sp. II2003 biofilms harboured mushroom-like structures, Roseobacter sp. IV3009 biofilms were quite homogeneous, Shewanella sp. IV3014 displayed hairy biofilms with horizontal fibres, whereasRoseovarius sp. VA014 developed heterogeneous and tousled biofilms. Conclusions This work led for the first time to the obtaining of four marine bacterial strains, potentially pioneering bacteria in marine biofilms, able to adhere to at least two different surfaces (polystyrene and glass) and to build specific 3D biofilms. The four selected strains are appropriate models for a better understanding of the colonization of a surface as well as the interactions that can occur between bacteria in a marine biofilm, which are crucial events for the initiation of biofouling.